1999
DOI: 10.1074/jbc.274.24.17342
|View full text |Cite
|
Sign up to set email alerts
|

p300/cAMP-responsive Element-binding Protein Interactions with Ets-1 and Ets-2 in the Transcriptional Activation of the Human Stromelysin Promoter

Abstract: In this paper we show that transcription factors Ets-1 and Ets-2 recruit transcription adapter proteins p300 and CBP (cAMP-responsive element-binding protein) during the transcriptional activation of the human stromelysin promoter, which contains palindromic Ets-binding sites. Ets-2 and p300/CBP exist as a complex in vivo. Two regions of p300/CBP between amino acids (a.a.) 328 and 596 and a. a. 1678 and 2370 independently can interact with Ets-1 and Ets-2 in vitro and in vivo. Both these regions of p300/CBP bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 68 publications
4
116
0
Order By: Relevance
“…Ets-1, -2 and the PEA3 family member, ER81 have been shown to recruit the transcription adaptor proteins p300 and CBP (Yang et al, 1998;Jayaraman et al, 1999;Papoutsopoulou and Janknecht, 2000;Foulds et al, 2004). More recently we have proposed that the steroid receptor coactivator, p160 protein, SRC-1 is a functional coactivator of Ets-2.…”
Section: Introductionmentioning
confidence: 99%
“…Ets-1, -2 and the PEA3 family member, ER81 have been shown to recruit the transcription adaptor proteins p300 and CBP (Yang et al, 1998;Jayaraman et al, 1999;Papoutsopoulou and Janknecht, 2000;Foulds et al, 2004). More recently we have proposed that the steroid receptor coactivator, p160 protein, SRC-1 is a functional coactivator of Ets-2.…”
Section: Introductionmentioning
confidence: 99%
“…Ets-1 binds various transcription factors, including Sp1 (Gegonne et al, 1993), PEBP2a/AML-1 (Giese et al, 1995), GHF-1/Pit-1 (Bradford et al, 1995), MafB (Sieweke et al, 1996), NF-kB, AP-1 (Thomas et al, 1997), and USF-1 (Sieweke et al, 1998). Despite its high degree of structural similarity with Ets-1, only one protein-protein interaction between Ets-2 and p300/CBP (Jayaraman et al, 1999) and two transcriptional cooperations with GATA3 (Blumenthal et al, 1999) or ATF/Jun family members (Cirillo et al, 1999) have been reported. Two Stat-Ets cooperations have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Promoter reporter assays, in vitro and in vivo protein-binding assays, EMSA and ChIP assays Procedures for GST-pull down assays and EMSA were as described (Jayaraman et al, 1999). For detecting the multiprotein complexes, nuclear extracts were prepared from SaOS2 cells after transfecting with expression plasmids expressing HA-p300, FLAG-YY1 and His-HDAC3 were incubated with an YY1 probe and in the presence of appropriate antibodies for 20 min.…”
Section: Cells Ad Vectors and Plasmidsmentioning
confidence: 99%